Sweethearts - Zarr, Sara (Little, Brown and Co., 2008)
After losing her soul mate, Cameron, Jennifer transformed herself from the unpopular fat girl into the beautiful and popular Jenna, but Cameron's unexpected return dredges up memories that cause both social and emotional turmoil.